Climate concerns for clinicians: evaluating harmful algal bloom knowledge and educational opportunities for health care provider students - Lund, Alexander; McNair, Carrie; McGowen, Chelsea; Lowman, Janel; Sobol, Robert; Parsons, Michael; Pierce, Jennifer (Frontiers in Medicine, 2025)
With increasing incidence of harmful algal blooms (HABs) and their associated illnesses such as ciguatera poisoning (CP), there is need for educating current and future clinicians. This study sought to assess medical and physician assistant (PA) students' knowledge, attitudes, and beliefs toward HABs and their related illnesses. A survey of medical students and PA students at the University of South Alabama (USA) was conducted using an online questionnaire on climate change, HABs/associated illnesses, and CP. Response rate was calculated using fully executed questionnaires. Frequency data was utilized for demographics and knowledge-based questions; stratified analysis was used for associations. Three hundred three medical students received the questionnaire; 27% (n = 81) completed it. One hundred seventy-one PA students received the questionnaire; 19% (n = 33) completed the survey. These students were demographically representative of their student bodies. Out of 10 questions regarding knowledge of HABs, the percent correct was 30.7% for medical students and 20.3% for PA students. 34.6% of medical students and 47.1% of PA students had never heard of HABs. 90.1% of medical students and 84.8% of PA students believed climate change will impact human health in the future and more knowledge is needed about the relationship between health and climate change. Seventy six percentage of medical students and 51.6% of PA students expressed that HAB education should be part of health professional school curriculum. Future clinicians have little knowledge of HABs and their associated illnesses despite recognizing that climate change is a vital health issue. Medical and health professional schools should consider adding HAB education for future clinicians.